Metabolomics in search of new biomarkers for health monitoring of preterm newborns - Rodrigues, Mariana Carreira (2020)
Chapter 1 is divided in 4 parts, comprising a first part referring to the definition of preterm, identifying its main associated risk factors and consequent health complications in short and long terms. In part 2 the applied methodology is presented, giving a brief introduction about the analytical and statistical methods used. The principles of the methodology used and state of the art are also described. Part 3 describes the importance of biomarkers in diagnostics, therapy and prognostics of disease. In part 4 the clinical potential of metabolomics in neonatology is described, referring the biofluids used and the main metabolic studies associated with preterm birth (PTB). This part concludes with a literature review of studies of premature infants and newborns, and premature infants compared to other disorders. Chapter 2 describes the experimental procedures used to perform this work, including group presentation, sample collection and preparation, sample acquisition and data processing. Chapter 3 characterizes the composition of newborn’s urine using Nuclear Magnetic Resonance (NMR) spectroscopy, which 49 metabolites were identified. Chapter 4 presents the metabolic study of preterm newborns to find markers related to prematurity at the time of birth. Metabolic variations at different stages of prematurity (extreme preterm (<28gestational weeks), very preterm (28<32 gestational weeks) and moderate to late preterm (32<37gestational weeks)) are presented. Chapter 5 deals with the metabolomic study of the development of preterm newborns over time, during their stay in hospital. Finally, the main conclusions of this work are present in Chapter 6, emphasizing the clinical potential of metabolomics in preterm urine for monitoring newborns during their hospital stay, in order to use new biomarkers of deviant behaviours indicative of health complications during that period.